Validity Development of Critical Thinking Skill Test Instruements on Running and Stationer Wave Materials - Setiani, Rahyu; Kafii, Muhammad Shokhibul; Dwikoranto, Dwikoranto (Universitas Negeri Surabaya, 2023)
This study aims to determine the feasibility of critical thinking skills test instruments on running wave and stationary material that meet good qualifications, including aspects of validity, reliability, discriminating power, level of difficulty, and student response tests. This research is a development with the ADDIE approach which stands for Analysis, design, development, implementation, and evaluation. This research was conducted at MAN 1 Mojokerto with a sample of 30 students. The test instrument was declared feasible based on three categories, namely based on expert judgment, reliability testing, and the level of students' critical thinking skills. The results obtained by the feasibility validity test of the three experts averaged 3.67. With a very decent category. This shows the instrument is feasible to use. This instrument is declared reliable for use with a reliability value of 0.70. The level of difficulty of the questions is in the medium category with sufficient discriminating power on average. The average result of students' critical thinking skills is 25%. This shows that students' critical thinking skills are in the low category. Based on these criteria, 9 questions in essay form have been declared good and suitable to be used to train students' critical thinking skills.